A vallás és egészség kapcsolatának szociológiai értelmezése (Szociológiai Szemle, 2024)
Sutides on religion and health form a significant research field in medical sociology. Researchers should, however, face many methodological problems when justifying empirically the relationship, among others, problems of definition, operationalization, validity and reliability of the measurements. Since the 1970s, a number of socio-epidemiological studies have justified that there is a beneficial relationship between religion (and spirituality in a broader sense) and health. Research investigated mortality and morbidity among Catholics, Protestants, Adventists, Mormons and in the Clergy. The potential mechanism of effect is rather complex and involves factors from behaviour control through social support to providing a frame for the interpretation of life. Further research on religion and health should provide a sophisticated understanding o f the role of reinterpreted religion in health.